(untitled) (Heritage, 2025)
After shooting documentaries with genre-based approaches directed at social issues and memory (youth and migration, socialist monuments in post-Yugoslav region), Jelena Radenović has further enriched her oeuvre with another documentary named And the River Still Flows (A Istok reka teče, 2023). The translation of the film’s poetic title into English, however, loses part of its meaning which is directed towards the geographical region of the Metohija valley, since the river’s name, whose literal meaning is East, is left out of title. Following the meandering flow of her early memory, this film nostalgically portrays the homeland of her ancestors that she used to visit as a child before the breakup of Yugoslavia. The paper analyzes this documentary from the angle of film studies and anthropology by categorizing its mode of representation, using Bill Nichols’ classification, primarily as performative, given that the author of the film is present in the material and that the embodied memory is used as an evocative source that directs the observer’s involvement with the topic, emptied of historical details. The film’s influence on cultural frames of representation of the tragedy of the exodus of Serbs from Kosovo and Metohija after the NATO bombing of the Federal Republic of Yugoslavia and the March Pogrom, is analyzed by delineating various narrative layers of symbolism referring to the meaning of home and its loss. Our goals are to outline visual and poetic sources through which reflexive nostalgia is achieved in the portrayal of memory which is being reassembled based on a personal family story about loss, through which belonging and national identification are reaffirmed. A summary of key geographical and cultural elements in the film reveals its underlying political message, which is directed towards a desire for multiethnic dialogue among Serbs and Albanians, affirming the capacity of the performative documentary mode to serve as a visual space for reflexive rethinking of ideological standpoints, as well as locating its constraints. Applied visual styles of nature’s anthropomorphization are compared with similar poetical formulations in art and are explained in relation to the documentary’s transformation of loss by means of figurative questioning of the opposition between nature and culture; therefore, the documentary is singled out as a unique transgenerational ecranization of home loss, thematically devoted to the question of Serbs in the disputed post-war region.